Comparative analysis of writing strategies between Malaysian and Indonesian students - Noor Azli Affendy Lee; Ryani Yulian; Nur Husna Serip Mohamad; Ufi Ruhama'; Rofiza Aboo Bakar (Universitas Syiah Kuala, 2025)
This study investigates the differences in writing strategies between upper secondary school students from rural schools in Penang, Malaysia, and Pontianak, Indonesia, to understand the influence of cultural and educational backgrounds on their approach to writing tasks in English. Utilizing a structured questionnaire with a Likert Scale, data from 109 Malaysian and 100 Indonesian students were analysed through descriptive statistics and t-tests for Equality of Means. The findings reveal significant differences in general, pre-writing, during-writing, and post-writing strategies between the two groups. Malaysian students exhibit a stronger inclination towards writing in their native language and utilizing bilingual dictionaries, while Indonesian students demonstrate a higher preference for writing in English during leisure, using English-to-English dictionaries, and relying on English grammar books. The study highlights the diverse approaches to language use and learning, suggesting potential cultural or educational influences shaping these practices. The data accentuates the importance of considering these contextual factors in enhancing writing instruction and suggests tailored educational interventions to address specific needs and practices. The findings also suggest educational interventions can improve planning and outlining skills, promote creative language use, and increase language resource usage. Educators should consider students cultural and educational contexts, tailoring strategies to diverse learning styles by integrating bilingual resources, promoting language experimentation, and emphasizing feedback and revision.